The Curricular Construction of Dance in Spain: A Content Analysis of Decree 156/2007 of the Valencian Community - De la Concepción Planas, Paula (2026)
This study examines the regulations governing Professional Dance Education in Spain, focusing on Decree 156/2007 of the Valencian Community, with the aim of analyzing the classical dance learning outcomes established for students specializing in contemporary dance and identifying curricular presences and absences from a critical perspective. Content analysis is used as a qualitative method through the review of regional legislative documents and the coding of objectives, contents, and assessment criteria. The results show that the curriculum is organized around a technical dimension of learning, in which categories such as body, skill, technique, technical mastery, and musicality stand out, highlighting the historical weight of classical dance as a foundational component even within the contemporary dance specialization. In addition, relevant absences are identified, such as the lack of explicit references to competencies, methodological principles, or the role of educational guidance professionals, together with a limited presence of approaches related to inclusion, body diversity, and gender perspective. It is concluded that the regulations reproduce traditional models focused on technique and meritocracy, hindering the incorporation of inclusive and contextualized pedagogical practices, thus revealing the need to update the curriculum.